Effect of an Olive Oil–Based Lipid Emulsion Compared With a Soybean Oil–Based Lipid Emulsion on Liver Chemistry and Bile Acid Composition in Preterm Infants Receiving Parenteral Nutrition: A Double-Blind, Randomized Trial. (August 2016) - Wang, Ying; Zhou, Ke-Jun; Tang, Qing-Ya; Hong, Li; Feng, Yi; Lu, Li-Na; Wang, Wei-Ping; Cai, Wei
Background : The pathogenesis of parenteral nutrition (PN)–associated liver dysfunction is multifactorial. Lipid emulsions may be one of the putative mechanisms. Our aim was to comparatively assess the effect of parenteral olive oil– and soybean oil–based lipid emulsions on liver chemistry and bile acid composition in preterm infants. Methods : We performed a double-blind, randomized clinical study in which 103 preterm infants were randomly assigned to PN using either soybean oil–based lipid emulsion (SO; n = 51) or olive oil (OO)–based lipid emulsion (OO; n = 52). The primary end point was liver chemistry. The secondary end point was the plasma bile acid composition. Results : One hundred infants completed this study. In the SO group, the serum direct bilirubin was significantly higher after PN for 7 days compared with the OO group. Bile acids increased over time in both treatment groups. However, specific differences in the change in bile acid composition over time were noted between groups. Conclusions : Differences in direct bilirubin and bile acid composition were observed over time between the 2 groups. Considering the long-term use of lipid emulsions in higher risk babies, these findings might be useful for understanding the pathogenesis of PN-associated liver dysfunction.